Current management practices and interventions prioritised as part of a nationwide mastitis control plan - Down, P.M.; Bradley, Andrew J.; Breen, J.E.; Hudson, C.D.; Green, Martin J. (BMJ Publishing Group, 2016)
The objectives of this study were to report performance and management data taken from a sample of UK dairy farms that have participated in the Agriculture and Horticulture Development Board Dairy Mastitis Control Plan (DMCP) and to identify important mastitis prevention practices that are not currently widely implemented. A total of 234 UK dairy herds were included in the study from which farm management and udder health data were collected. Herds were grouped according to their mastitis epidemiology and could be classed as (i) environmental dry period (EDP) (i.e. environmental pathogen with majority of infections being acquired during the dry period), (ii) environmental lactation (EL), (iii) contagious dry period (CDP) or (iv) contagious lactation (CL). The results of this study showed that many mastitis-related management practices that are generally considered to be important were not widely performed. A better understanding of those practices not widely adopted by UK dairy farmers at present may aid practitioners in identifying and overcoming potential barriers to improved mastitis control.